Mejoramiento genetico de yuca para productividad - Kawano, K (International Center for Tropical Agriculture, 1977)
When developing breeding programs, it is necessary to take into account certain characteristics of the crop such as method of propagation (vegetative or sexual) and physiological factors affecting yield (i.e., the roots in cassava). Genetic improvement, as well as the specific breeding objectives for cassava, is defined. The biological characteristics of cassava, factors of genetic variation and selection and different methods for evaluating material are discussed. After 4 years` work the cassava breeding program at CIAT has developed hybrid lines yielding more than 50 tons/ha/yr (fresh wt) and more than 30 tons on oxisols in the Llanos Orientales of Colombia, which represents a 50 percent increase over local varieties. (CIAT)